Le mouvement gai et lesbien américain face au SIDA - Marche, Guillaume (L'Homme & la Société, 2002)
Divided between essentialism and constructivism, the mobilization of united-statesian homosexuals becomes a real social movement when it goes beyond the opposition between integrationism and differentialism. Thanks to a complex identity forged by ACT-UP, it has been able in this way to resist AIDS. A comparison between San Francisco and New York shows that the initiative comes from the bottom up. Collective action is most effective as it takes account of differences (such as ethnicity) between homosexuals. This requirement has been dictated by the evolution of AIDS since the 1990s. It is, therefore, in stressing the subjectivity of the actors that the gay and lesbian movement can continue and contribute to social change in the United States.
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; cours; discipline; discours dominant; histoire et politique; homophobie; hétérosexisme; identités LGBTQIA2+; lesbianisme; premier cycle; périodes historiques; queer; régions géographiques; santé; sexualité; shm4000; systèmes d'oppressions; thématiques; états-unis

Les familles homosexuelles aux États-Unis : dissolution d'un mouvement social ou redéfinition de sa portée politique? - Marche, Guillaume (Revue française d'études américaines, 2003)
Families are a challenge to the lesbian and gay movement in the United States, since homosexuality is largely construed as antithetical to "the family". By creating a wide variety of alternative families gays and lesbians however articulate an identity claim which may not be framed exclusively either in terms of assimilationism, or of differentialism. For this reason these alternative families present American society with a transformative potential which is in a position to exert its influence beyond the bounds of the gay and lesbian community. Far from being a hindrance in terms of efficiency, the very fact that these families constitute a private locus of gay and lesbian experience furthermore contributes to the lesbian and gay movement's expressive dimension, which is of crucial strategic importance in contemporary American society.
Keywords: LGBTQIA2+; amériques; approches et analyses; cours; discipline; discours dominant; famille; familles homoparentales; his4443; homoparentalité; hétérosexisme; identités LGBTQIA2+; lesbianisme; mouvements de libération; mouvements lgbt; mouvements queer; mouvements sociaux; parentalité; patriarcat; philosophie politique; premier cycle; queer; régions géographiques; sciences humaines; sciences sociales; systèmes d'oppressions; thématiques; états-unis; études américaines